2014
DOI: 10.1007/s00704-014-1242-8
|View full text |Cite
|
Sign up to set email alerts
|

The change of global terrestrial ecosystem net primary productivity (NPP) and its response to climate change in CMIP5

Abstract: Using global terrestrial ecosystem observation and proxy data for net primary productivity (NPP), leaf area index (LAI), and climate data, we compared simulated NPP, LAI, and major climatic factors and explored the relationship between their variations in historical scenarios of ten Coupled Model Intercomparison Project (CMIP5) models. The results showed that global spatial patterns of the simulated terrestrial ecosystem and climate are consistent with proxy data, but the values have some differences for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
2
13
0
5
Order By: Relevance
“…The uncertainty of the HadGEM2-ES model was the largest, and the uncertainty of the MIROC5 model was the smallest. These results are consistent with those obtained by Li, Lu, Zhang, Liu, Gao, and Ao [71] and Fu et al [111]. In fact, multiple studies have found large uncertainty associated with the NPP of the global terrestrial ecosystem.…”
Section: Quantifiable Sources Of Uncertaintysupporting
confidence: 92%
See 1 more Smart Citation
“…The uncertainty of the HadGEM2-ES model was the largest, and the uncertainty of the MIROC5 model was the smallest. These results are consistent with those obtained by Li, Lu, Zhang, Liu, Gao, and Ao [71] and Fu et al [111]. In fact, multiple studies have found large uncertainty associated with the NPP of the global terrestrial ecosystem.…”
Section: Quantifiable Sources Of Uncertaintysupporting
confidence: 92%
“…Precipitation was found to be the second-most important factor (R > 0.017). These results are supported by those of Li et al [71] and Li et al [72], who used the Climate Model Intercomparison Project (CMIP5) multipattern to explore the response of global terrestrial NPP to climate change during the historical period from 1850-2005. However, our study also found that as emissions increased, the correlation between solar radiation and alterations in NPP content changed from positive under the low-emission scenario (RCP2.6) to negative under the high-emission scenario (RCP8.5).…”
Section: Impacts Of Climate Variations On Net Primary Productivity Insupporting
confidence: 75%
“…Our simple models also have limitations; for example, we do not attempt to represent growth (or growth respiration) responses to temperature variation, nor do we attempt to extrapolate from leaf‐level respiration to other plant tissues or ecosystem‐level fluxes. It is expected that total global leaf area will increase under climate change (Betts et al ., ; Li et al ., ), which would increase total leaf and autotrophic respiration (as well as photosynthesis) independently from changes that occur at the leaf level. Also, our climate simulations assume that daytime and nighttime temperatures will change by the same amount, but many projections indicate that daily minimum temperatures will increase more than daily maximum temperatures (IPCC, ).…”
Section: Discussionmentioning
confidence: 99%
“…Through modeling and simulation, one could reveal the quantitative changes and trends of NPP caused by climate changes. It was why the research of NPP model had attracted a vast amount of attention (Li et al 2015). This study establishes an estimation model for southern grassland NPP by using the statistical analysis results of southern grassland NPP and precipitation and temperature combined with biological process.…”
Section: Discussionmentioning
confidence: 99%